EKSPLORASI WUJUD TRADISI MAULID NABI SEBAGAI MEDIUM PEMAHAMAN SEJARAH NABI MUHAMMAD PADA SEKOLAH DI KOTA BANDUNG - FAIZIN, M. NUR; FIRDAUS, ENDIS; FAKHRUDDIN, AGUS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The commemoration of the Prophet Muhammad's birthday (Maulid Nabi) is a tradition practiced and maintained by Muslims to celebrate the birth of Prophet Muhammad SAW, particularly among school communities in Indonesia. This study aims to explore the form of the Maulid tradition as a medium for understanding the history of Prophet Muhammad in schools in Bandung, especially at the junior high school level. This research uses a qualitative method with a field research approach. The subjects of the study include students and teachers at schools that are the focus of this research, namely SMP Negeri 49 Bandung, SMP Pasundan 4 Bandung, and SMP PGII 1 Bandung. Data collection techniques were conducted through interviews, observations, and documentation during the activities. This research emphasizes the importance of integrating religious traditions into educational programs to strengthen students' religious identity and provide additional insights into the history of Prophet Muhammad SAW. Based on the research findings, various activities in the commemoration of Maulid, such as the recitation of Barzanji, singing of sholawat, art performances, and interactive lectures, play an important role in providing students with additional insights into the history of Prophet Muhammad SAW, especially regarding his character and his struggles in spreading the teachings of Islam. Moreover, the active participation of students and teachers can create an enjoyable learning environment during the Maulid Nabi commemoration. In the future, further research is expected to explore more innovative teaching methods in Islamic education and analyze the long-term impact of this tradition on students' character development. ABSTRAKPeringatan Maulid Nabi merupakan tradisi yang dilaksanakan dan dipelihara oleh umat Islam untuk memperingati kelahiran Nabi Muhammad SAW, khususnya di kalangan warga sekolah pada satuan pendidikan di Indonesia. Penelitian ini bertujuan untuk mengeksplorasi wujud tradisi Maulid sebagai medium pemahaman sejarah Nabi Muhammad di sekolah-sekolah Kota Bandung, khususnya pada jenjang SMP. Jenis penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian lapangan (field research). Subjek penelitian terdiri atas siswa dan guru di sekolah-sekolah yang menjadi fokus penelitian, yaitu SMP Negeri 49 Bandung, SMP Pasundan 4 Bandung, dan SMP PGII 1 Bandung. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi selama kegiatan berlangsung. Penelitian ini menekankan pentingnya mengintegrasikan tradisi keagamaan ke dalam program pendidikan untuk memperkuat identitas keagamaan siswa serta memberikan wawasan tambahan tentang sejarah Nabi Muhammad SAW. Berdasarkan hasil penelitian, berbagai kegiatan dalam peringatan Maulid, seperti pembacaan Barzanji, nyanyian sholawat, pentas seni, dan ceramah interaktif, berperan penting dalam memberikan wawasan tambahan bagi siswa tentang sejarah Nabi Muhammad SAW, terutama mengenai akhlak beliau dan perjuangannya dalam menyebarkan ajaran Islam. Selain itu, partisipasi aktif siswa dan guru dapat menciptakan lingkungan belajar yang menyenangkan selama peringatan Maulid Nabi. Di masa depan, penelitian selanjutnya diharapkan dapat mengeksplorasi metode pengajaran yang lebih inovatif dalam pendidikan agama Islam serta menganalisis dampak jangka panjang dari tradisi ini terhadap pengembangan karakter siswa.